Hubungan Motivasi Menjadi Perawat dengan Prestasi Belajar Mata Kuliah KDM dan KDK pada Mahasiswa DIII Keperawatan Baitul Hikmah Bandar Lampung - Sri Suharti (Jurnal Kesehatan Panca Bhakti Lampung, 2019)
Motivation is anything required including verbally, physically, and psychologically which encourage someone to do something for expressing and defending into a specific goal. The motivation in education process is important so that deep and complete understanding is required so that Baitul Hikmah Academy of nursing in Bandar Lampung will be better. The objective of this research was to find out the correlation between motivation of becoming nurse and learning achievement of KDM and KDK subjects of students in Baitul Hikmah DIII of Nursing Science in Bandar Lampung in 2014.This was a descriptive correlation research with cross sectional approach. Population was 316 students of first, second, and third year in Baitul Hikmah Academy of Nursing in Bandar Lampung. Samples were 176 respondents. Data were analyzed with bivariate analysis by using chi square test.The statistic test results showed that there was no correlation between motivation of becoming nurse and learning achievement of KDM (p-value = 1.000) and KDK (p-value = 0.845) subjects of students in Baitul Hikmah DIII of Nursing Science in Bandar Lampung in 2014. The researcher expects education institution to be able to provide nursing education by improving education quality in Baitul Hikmah Academy of Nursing in Bandar Lampung by giving motivation and direction so that students’ achievements will be improved. Academic consultants should enhance their monitoring and counselling for students.